Depression, intercorporeality, and interaffectivity - Fuchs, Thomas (Journal of consciousness studies, 2013)
According to current opinion in western psychopathology, depression is regarded as a disorder of mood and affect on the one hand, and as a distortion of cognition on the other. Disturbances of bodily experience and of social relations are regarded as secondary to the primarily ‘inner’ and individual disorder. However, quite different concepts can be found in cultures whose members do not experience themselves as much as separate individuals but rather as parts of social communities. Disorders of mood or well-being are then conceived less as intra-psychic, but rather as bodily, interpersonal, or atmospheric processes.
Gesehen am 15.06.2021